Effect of dielectric materials on integrated lens antenna for millimeter wave applications. Issue 4 (11th January 2019) - Kamran Saleem, Muhammad; Xie, Mingyang; Alkanhal, Majeed A. S.; Saadi, Muhammad
Abstract: The effect of different dielectric materials on the performance of integrated lens antenna (ILA) operating in millimeter wave region (60 GHz) is presented. The ILA is composed of a rectangular microstrip antenna and an extended hemispherical dielectric lens. The gain of microstrip patch antenna (MPA) operating in 60 GHz band (58.25‐62.5 GHz) is enhanced from 7.4 to 15 dBi by integrating an extended hemispherical dielectric lens having a radius of 1 λo . The effect on ILA with different dielectric materials that is, teflon, rexolite, ABS (3D printed), polyethylene, polypropylene, and polystyrene is studied. A prototype ILA, consisting of MPA integrated with extended hemispherical dielectric (teflon) lens is developed and tested to validate simulation results. The results of change in dielectric lens size (radius, height) are also presented.